Co-creating social innovation in quadruple helixes: evidence from Sweden - Öberg, Åsa; Albats, Ekaterina; Stefan, Ioana; Johansson, Peter E. (Proceedings of ISPIM Conferences, 2021)
In an increasingly globalized world, the challenges of society need to be tackled not by single organisations but by a multitude of stakeholders. Universities can contribute by extending their role and by collaborating with external stakeholders. This study employs qualitative methods to explore how a university engages with its innovation ecosystem through two different projects.The findings, connected to the development of educational and digital systems,show: 1) evidence of two extreme approaches to external stakeholder engagement and 2) three levels of tensions (multi-layered tensions) - on an overarching level, between stakeholder groups, and within groups of stakeholders. The contribution connects to literature on open innovation, quadruple helixes and lastly to university social innovation, especially responsibility diffusion.
Keywords: Co-création; Europe; Quadruple helix approach